2018
DOI: 10.1186/s13023-018-0954-8
|View full text |Cite
|
Sign up to set email alerts
|

Arginine does not rescue p.Q188R mutation deleterious effect in classic galactosemia

Abstract: BackgroundClassic galactosemia is a rare genetic metabolic disease with an unmet treatment need. Current standard of care fails to prevent chronically-debilitating brain and gonadal complications.Many mutations in the GALT gene responsible for classic galactosemia have been described to give rise to variants with conformational abnormalities. This pathogenic mechanism is highly amenable to a therapeutic strategy based on chemical/pharmacological chaperones. Arginine, a chemical chaperone, has shown beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…As such they have been dubbed “natural gene therapy” and “nature's proof of principle that you can fix those mutations” in the case of Wiskott–Aldrich syndrome (WAS). 97 Additional examples include the p.Q188R mutation in classic galactosemia 98 that gives rise to a protein with lower conformational stability and lower catalytic activity 99 and p53. 100 Drugs mimicking the allosteric effects of these mutants may rescue function.…”
Section: To-date Unexplored Pi3kα Therapiesmentioning
confidence: 99%
“…As such they have been dubbed “natural gene therapy” and “nature's proof of principle that you can fix those mutations” in the case of Wiskott–Aldrich syndrome (WAS). 97 Additional examples include the p.Q188R mutation in classic galactosemia 98 that gives rise to a protein with lower conformational stability and lower catalytic activity 99 and p53. 100 Drugs mimicking the allosteric effects of these mutants may rescue function.…”
Section: To-date Unexplored Pi3kα Therapiesmentioning
confidence: 99%
“…Arginine supplementation, known for its effect as an aggregation inhibitor [ 82 ] has been studied as a potential therapeutic approach for classic galactosemia. Despite promising results of this chemical chaperone in a bacterial model [ 83 ], in a pilot study with 4 patients carrying the NM_000155.4: c.563A>G (p.Gln188Arg) mutation, arginine did not lead to improved GALT stability nor GALT activity levels as there was no improvement in galactose oxidation capacity [ 4 , 84 ].…”
Section: Potential Therapiesmentioning
confidence: 99%
“…Initial studies suggested that non-specific binding of the amino acid arginine stabilises GALT [ 100 ]. Unfortunately, further work demonstrated that this is not the case [ 101 ]. In contrast, PCs bind to specific sites.…”
Section: Potential In the Treatment Of Galactosemiamentioning
confidence: 99%